A case of coronoidectomy simulated using threedimensional models and surgical guide for severe trismus caused by bilateral coronoid hyperplasia. Issue 6 (November 2020) - Inoue, Kazuya; Nakano, Hiroyuki; Yonenaga, Takatoshi; Ogura, Ayano; Omori, Michi; Yamamoto, Naofumi; Nakajima, Yoichiro; Ueno, Takaaki
Abstract: Hyperplasia of the mandibular coronoid process is a clinical condition that causes an indolent trismus by elongated coronoid processes that impinge on the zygomatic medial surface when opening the mouth. We report a case of hyperplasia of the mandibular coronoid process in which a 3D printer was used to create a jaw model and a surgical guide for performing bilateral coronoidectomy, i.e., a simulated surgery before the actual surgery, with good results. The patient was a 60-year-old man who had trismus since adolescence. The trismus did not improve since many years; hence, he was referred to our department. His temporomandibular joint movements were normal. Panoramic radiographs and CT images showed extension of the muscular processes beyond the zygomatic arch, and the patient was diagnosed with hyperplasia of the mandibular coronoid process. Therefore, we considered that preoperative surgery simulation was necessary to perform the operation more safely. The jaw model and the surgical guide for setting the resection line of the coronoid process were prepared. We evaluated the morphology of the mandibular coronoid process and simulated the surgery before performing bilateral coronoidectomy. The maximum mouth opening after intraoperative resection was 43 mm. The training of mouth opening was continued, and the maximum mouth opening at 6 months postoperatively was 30 mm. Thus, we believe that the surgery could be performed more reliably by preparing the 3D model preoperatively, performing surgical simulation, and creating a surgical template.